Performance Evaluation of Irrigation Automation for Cultivation System of Rice Intensification (SRI) Combined with Jajarlegowo System: Theories, Methods, and Techniques - N. Gupta; Encep Kamal; Kamsa Hambari; M. Rikja Hamdani; Pera Maeda Ningsih; Dewi Sartika (Nusa Putra University, 2019)
The objective of this article is to review and represent about automation irrigations that have been gained in irrigation system performance evaluation for cultivation System of Rice Intensification (SRI) combined with Jajarlegowo System. This paper is based on the literature that is concerned with concepts, techniques, and methodologies applied to the automation irrigation and their performance in Indonesia. The development of automation irrigation for paddy field in Indonesia was presented and it was discussed. Several studies of automatic irrigation systems have been conducted in Indonesia. The results showed that the use of irrigation automation system combined with a system of rice intensification (SRI) and combined with jajarlegowo can increase rice productivity. This method is effective because the rice plants are watered according to their needs so that the growth becomes good. The method of irrigation automation is carried out using a water level control system adapted to the age of the rice plant. Water level sensors, irrigation actuators, and drainage actuators are installed in paddy fields to support the irrigation automation. In the application directly in the paddy fields owned by Indonesian farmers, this has not been done thoroughly. The main obstacle from the observation result of the research shows that automatic irrigation system technology has not shown any real difference compared to conventional irrigation. In addition, this automatic irrigation system should also be accompanied by human resources trained in its use and maintenance.